Determination of Tariffs For Managing Toxic And Hazardous Waste To Improve The Quality of The Tourism City Semarang, Indonesia - Nining Yuniati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The garbage problem is never solved in various cities across Indonesia. This research focuses on specific waste, including toxic and hazardous waste. The study aims to determine the investment value and toll fees for the tourism area in Semarang, Central Java, Indonesia. So far, there is no proper mechanism because, according to government regulations, the government has the obligation to be the main responsible party. This study was conducted to find appropriate alternative treatments that are more implementable and can be carried out immediately. The survey was conducted in 16 districts within the city area, involving waste management communities or relevant agencies. Based on calculations at the household level, it was found that toxic and hazardous waste generation is 1006.25 tons per year. Per household, this ranges from 20 kg to 118 kg per year. This amount is very dangerous in increasing environmental, water, and soil pollution. Considering waste management practices, the required investment value is USD 1.46 million. Based on the polluter pays principle, the established collection fee per household is only USD 1.61 per kilogram per year, or IDR 26,571. This amount is very large if the government bears the entire cost, but through a participatory management system, the handling of toxic and hazardous waste will become easier.